2020
DOI: 10.1080/21623945.2020.1817278
|View full text |Cite
|
Sign up to set email alerts
|

RAGE signalling in obesity and diabetes: focus on the adipose tissue macrophage

Abstract: The advanced glycosylation end product receptor (RAGE) acts as a recognition receptor and interacts with different types of ligands that form and accumulate in the tissues and circulation, such as diabetes, inflammation, insulin resistance, and obesity. In these environments, RAGE is expressed on the surface of various cells associated with tissue disturbance. This review mainly summarizes the characteristics of RAGE-related signalling, with a particular emphasis on the role of RAGE in the development of obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Moreover, inflammatory macrophages disrupt ECM homeostasis, which leads to fibrosis (2). Lastly, advanced glycation end-products (AGE) that are increased in obese diabetic patients, impact both adipocyte and immune cells functions, as both cell types express the receptor for AGE (RAGE) (73,74). On the whole, inflammation in AT is triggered by several integrated mechanisms and involves the various cell subsets in the AT, i.e.…”
Section: Immune System Activation and Inflammatory Activity Of At In Obese Contextsmentioning
confidence: 99%
“…Moreover, inflammatory macrophages disrupt ECM homeostasis, which leads to fibrosis (2). Lastly, advanced glycation end-products (AGE) that are increased in obese diabetic patients, impact both adipocyte and immune cells functions, as both cell types express the receptor for AGE (RAGE) (73,74). On the whole, inflammation in AT is triggered by several integrated mechanisms and involves the various cell subsets in the AT, i.e.…”
Section: Immune System Activation and Inflammatory Activity Of At In Obese Contextsmentioning
confidence: 99%
“…RAGE belongs to the immunoglobulin superfamily and is expressed in several cell types including alveolar, neuronal, endothelial and immune cells (44)(45)(46)(47). Of note, RAGE expression is increased in most of the pathological conditions associated with COVID-19 severity, such as ageing (48,49), diabetes (50), obesity (51)(52)(53), atherosclerosis (54), cancer (55), chronic obstructive pulmonary disease (56) and ARDS (57).…”
Section: Discussionmentioning
confidence: 99%
“…Initially designated as a decoy receptor for the Advanced Glycation End Products generated during hyperglycemic states, RAGE has currently been acknowledged as a signaling receptor for a number of ligands, including S100A7 [31]. RAGE pathway is activated in conditions of de-regulated IGF/Insulin signaling and participates to the establishment of low-grade chronic inflammation and insulin resistance [20,50]. The S100A7/RAGE pathway has been shown to support neoplastic progression in diverse human tumors, including BC.…”
Section: Discussionmentioning
confidence: 99%
“…When released in the extracellular milieu, S100A7 acts as a cytokine-like molecule binding to its receptor RAGE (Receptor for Advanced Glycation End Products), a transmembrane protein belonging to the immunoglobulin superfamily [19]. Previous studies have shown that RAGE signaling is aberrantly activated in conditions of de-regulation of the IGF/Insulin axis, like obesity and T2DM [20]. Furthermore, an activated S100A7/RAGE pathway has been shown to promote angiogenic effects and facilitate breast metastasis dissemination [12].…”
Section: Introductionmentioning
confidence: 99%